Seção Técnica Centro de Convivência Infantil “Cantinho Feliz” - Almeida, Rute Honória dos Santos; Scaranelo, Elaine Sarjorato; Caetano, Eliane Marques; Damico, Fernanda Justi; Dias, Lidiane Cezario Romero; Silva, Marcel Vicente da; Lalucce, Nívea Maria Parpinelli; Vitório, Patrícia Lara Dias; Poliselli, Sônia Aparecida (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Rute Honória dos Santos Almeida